Preparation of ceramic membranes from surface modified tin oxide nanoparticles - Belin, S.; Santos, LRB; Briois, V; Lusvardi, A.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Chartier, T.; Larbot, A. (Elsevier B.V., 2003)
The preparation of crack-free SnO2 supported membranes requires the development of new strategies of synthesis capable to allow controlled changes of surface chemistry and to improve the processability of supported layers. In this way, the controlled modification of the SnO2 nanoparticle surface by adding capping molecules like Tiron(R) ((OH)(2)C6H2(SO3Na)(2)) during the sol-gel process was studied, aiming to obtain high performance membranes. Colloidal suspensions were prepared by hydrolyzing SnCl4.5H(2)O aqueous solution with NH4OH in presence of Tiron(R). The effect of the amount of Tiro(R) (from I to 20 wt.%) on the structural features of nanoparticles, powder redispersability and particle-solution interface properties was investigated by X-ray powder diffraction (XRPD), extended X-ray absorption fine structure (EXAFS), quasi-elastic light scattering and electrophoretic mobility measurements. XRPD and EXAFS results showed that the addition of Tiron(R) up to 20 wt.% to colloidal suspensions does not affect the crystallite size of SnO2 primary particles, determined around 2-3 nm. This value is comparable to the hydrodynamic size measured after redispersion of powder prepared with amount of Tiro(R) higher than 7.5 wt.%, indicating the absence of condensation reactions between primary particles after the initial precipitation step. As a consequence the powder with amount of Tiron(R) > 7.5 wt.%, can be fully redispersed in aqueous solution at pH greater than or equal to I I until a nanoparticle concentration of 6 vol.%. The electrophoresis measurements showed a decrease of the isoelectric point by increasing the amount of grafted Tiron(R) at the SnO2 nanoparticle surface, resulting in negatively charged particle-solution interface in all the studied pH range (2-11). These features govern the gelation process favoring the preparation of crack-free SnO2 supported membranes. The control exercised by Tiron(R) modifying agent in the aggregation process allows the fine-tuning of the porosity, from 0.124 to 0.065 cm(3) g(-1), and mean pore size, from 6.4 to 1.9 nm, as the amount of grafted molecules increases from 0 to 10 wt.%. In consequence, the membrane cut-off determined by filtration of polyethylene glycol standard solutions can be screened from 1500 to 3500 g mol(-1). (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: ceramic membranes; powder redispersion; nanoparticles; surface modification; sol-gel